Effect of mulching on web blight of beans in Costa Rica - Galindo, J.J.; Abawi, G.S.; Thurston, HD; Galvez, G (Scientific Societies, 1983)
Mulching was highly effective and superior to chemical treatments for the control of web blight (WB) caused in beans by Rhizoctonia solani, the imperfect state of Thanatephorus cucumeris. Plots were established in fields with a history of repeated incidence of WB. Soilborne sclerotia and colonized debris spread by splashing rain were the main sources of inoculum for WB in these fields. Mulching with rice husks (2.5 cm thick) greatly reduced splashing of inoculum and lowered disease severity. At harvest, severity of WB in nontreated and mulched plots planted to cultivar Porrillo 70 was 100 and 13%, and seed yield was 0 and 655 kg/ha, respectively. In a second field with a lower level of inoculum, yield in the nontreated and mulched areas averaged 273 and 835 kg/ha, respectively. Similar results were obtained with cultivar Mexico 27. Mulching with rice husks was superior to PCNB soil drench (40 kg 75 WP/ha) in controlling WB. Seed treatment with benomyl (1 g benomyl, 50% WP, per kilogram of seeds) and soil application of paraquat (1 kg a.i./ha) were ineffective. The local production practice of “frijol tapado,” in which seeds are broadcast in vegetation that is later cut and left as mulch, was as effective as rice husk mulching in reducing the incidence and severity of WB, but yields were lower.